Aspek Hierarki Kebutuhan Pada Tokoh Utama Dalam Novel Iyan Bukan Anak Tengah Karya Armaraher - Nuriski Septiani; Annisa Puspita; Eva Dwi Kurniawan (Universitas Palangka Raya, 2024)
In the novel Iyan Bukan Anak Tengah by Armaraher, the main character, Iyan, is a middle child who receives different treatment from his parents, from various aspects of the hierarchy of needs, such as physiological needs, a sense of security, social needs, self-esteem needs, to self-actualization in the character, so that during his teenage years Ian did not achieve self-actualization because his basic needs were not met. This research aims to look at the process of achieving aspects of the hierarchy of needs in the character Iyan in the novel Iyan Bukan Anak Tengah by Armaraher. This research looks at how the character can fulfill aspects of the hierarchy of needs to achieve self-actualization. This research uses a quantitative descriptive method, by analyzing words and sentences of text using Abraham Maslow's Hierarchy of Need theory. The results of this research show that the character Riyan did not fulfill the hierarchy of needs aspect during his teenage years so that the character Ian did not obtain self-actualization during adolescence, but the character Riyan fulfilled the aspect of the hierarchy of needs in adulthood, thus obtaining self-actualization during the character's adulthood.